Sub carrier multiplexed system for radio over fiber technology - S.M.Idrus, author; M.Arsat, author; A.S.Supaat, author; International Conference on Knowladge Based Development (2008 : United, Arab Emirates)i (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL